Skin Changes in Iatrogenic Cushing’s Syndrome: A Detailed Case Analysis - Earlia, Nanda; Maulida, Mimi; Vella, Vella; Pradistha, Aldilla; Wisesa, Wizurai; Razaq, Abdur; Ikram, Tubagus Pasca Faiz; Rahmatillah, Muhammad Zahrul; Farsa, Bianda Sabrina; Alghani, Fajri (Indonesian Journal of Case Reports, 2024)
Cushing's syndrome can lead to various skin complications. Iatrogenic Cushing's syndrome is a condition caused by excessive exogenous glucocorticoid exposure. This case report presents a patient with a history of Cushing's syndrome and long-term corticosteroid use who developed multiple skin manifestations. A 20-year-old male presented with erythematous purulent lesions on the face, neck, chest, and back. Concurrently, the patient developed purplish-red striae on the chest, abdomen, arms, and legs. Physical examination revealed erythematous nodules and pustules, along with atrophic striae. Laboratory tests showed leukocytosis with a left shift and hypokalemia. Radiological investigations revealed lumbar spondylosis and cardiomegaly. The patient was treated with a combination therapy, including topical and systemic medications, and showed significant improvement in skin lesions. This case highlights the importance of a comprehensive evaluation for patients presenting with unusual skin lesions. A thorough history, physical examination, and laboratory investigations are crucial to identify underlying conditions and initiate appropriate treatment.